Rectal carcinoid tumor with bone marrow and osteoblastic bone metastasis: A case report - Metin ÖZKAN; Özlem ER; İ. Ökkeş KARAHAN and Kemal DENİZ and Ramazan COŞKUN and Can KÜÇÜK and Alper YURCİ and Mustafa ALTINBAŞ (Turkish Journal of Gastroenterology, 2019)
-